Educational experiences and academic achievement of Asian Indian American students in a Midwestern university town in the United States: a multiple case study - Chakrabarti, Leena (Kansas State University, 2008)
There is a paucity of research on Asian Indians (AI) and Asian Indian Americans (AIA) and their experiences in the American school system. Studies suggest that the educational experiences of Asian Indian American students are related to Asian Indian parents' cultural background, and acculturation into the host society. Previous research also shows that Asian Indian students excel academically. However, the researcher has from personal experience seen that there is a variation in the experiences and academic performance of Asian Indian American students in the middle and high schools. This study describes the educational experiences and the academic achievements of Asian Indian students in a middle and high school district in a Midwestern college town. It uses the multiple case study design, which results in a picture of the commonalities among these Asian Indian students as well as their unique individual experiences. The researcher studies the experiences that the Asian Indian students have in school through student, parent and teacher feedback. Nine Asian Indian American students are interviewed in detail, eight of their parents are surveyed with detailed electronic surveys, and five core curriculum teachers were surveyed with a detailed email survey questionnaire. This study reveals three major themes, namely, the struggle for self-identity in the AIA students, the various definitions of academic success and success in life; and the role and responsibility of the school district in nurturing these concepts of self-identity and academic success. The recommendations for schools and the teachers are to modify the curriculum to include AIA information as part of the regular curriculum. Asian Indian and Asian Indian American culture, history, geography, literature, must be taught regularly. Teachers must conscientiously incorporate the contributions of AIs and AIAs as a part of the regular curriculum. The recommendation for AI parents is to realize that their children are Americans of Indian origin, and not Asian Indians. The recommendations for further research are an inquiry into the absence of AIA information in the curriculum, a longitudinal study to follow the success of AIA students in later life.
Keywords: Multicultural education; Asian Indian Americans; Asian Indians; Education, Bilingual and Multicultural (0282); Education, Curriculum and Instruction (0727); Education, Secondary (0533)